Case Report and Review of Keratoameloblastoma – A Rare Type of Keratin Producing Odontogenic Neoplasm - Debasish Pramanick (Journal of Orofacial Research, 2021)
Ameloblastoma is a slow-growing, locally invasive odontogenic tumour having odontogenic epithelial origin. Some histological variants of ameloblastoma show keratinization such as - Acanthomatous ameloblastoma, Keratoameloblastoma and Papilliferous Keratoameloblastoma. Among these, Keratoameloblastoma is a very rare tumour. Here, we present a case of Keratoameloblastoma in a 45-year-old female patient. Clinically, there was an extra-oral bony hard, tender swelling involving symphyseal and right para-symphyseal region of the mandible. Intraorally, there was a tender swelling in the dentoalveolar region with buccal cortical plate expansion which extended from 32 to 45 tooth region. Focal area of ulceration was also seen intraorally. Based on the clinical, radiological and histopathological features, Keratoameloblastoma was diagnosed. So, each and every case of Ameloblastoma should be judiciously examined for any histopathological metaplastic changes and also to be treated accordingly to prevent recurrence.